The evaluation of Fourier transform infrared spectroscopy (FT-IR) for the determination of total phenolics and total anthocyanins concentrations of grapes - Lochner, Elana (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScAgric (Viticulture and Oenology))--Stellenbosch University, 2006